The Impact of Brand Advertising with Celebrity Endorsement in Retail Industry on Indonesia Consumer Behavior - Fadhillah, Hannah; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2017)
Abstract –  Indonesians market are believed to have great opportunity, the population is young, growing and rapidly urbanizing, making it one of the fastest-growing consumer markets in the world. Indonesian retail industry has become more competitive and many brands are competing to attract consumers through advertising. Consumers are exposed with so many advertising and each brands need to compete to gain their intention. Many brands in Indonesia have used celebrity endorsement as one way to promote their products, especially in retail industry. The research was conducted by data analysis utilizing the result of in-depth interview and questionnaire. The author attempted to find correlation between brand advertising with celebrity endorsement and consumer behavior, to assure and create solutions through marketing strategies that would be done by the retail company, both in order to improve the performance of the company's current condition and future business development. The results are brand advertising with celebrity endorsement effect consumer in identifying the brand or product, influence consumers’ perceptions and thought about the brand or product in terms of image and performance and influence the consumer to purchase the product. Marketers need to choose the celebrity to present their brand carefully. The celebrity’s character should match with the brand personality and target audience. Marketers and retail companies can create the marketing strategy and consider brand advertising with celebrity endorsement. Further research to focus in each product category level of retail industry need to be covered.Keywords: Marketing, Brand, Advertising, Celebrity Endorsement, Consumer Behavior